Analysis of Indonesian Islamic banking performance using Sharia Maqasid Index and simple additive weighting rating - Ahmad Dahlan Malik; Muhammad Asyhad; Nurul Jannah; Wulan Nuraini (Muqtasid: Jurnal Ekonomi dan Perbankan Syariah, 2024)
This study aims to analyze the performance of Islamic Commercial Banks (ICB) and Islamic Banking Units (IBU) in Indonesia in 2021-2023 based on the Sharia Maqasid Index (SMI) and Simple Additive Weighting Rating (SAWR). Assessment of the performance of ICB and IBU in the Annual Report so far is only based on financial ratios, so it cannot evaluate the basic principles of Islamic banks. Therefore, the SMI and SAWR approaches are used to measure the performance of Islamic banks. The object of this research is 13 ICB and 20 IBU registered with OJK (Financial Services Authority). The results showed that the highest total score was Bank Mega Syariah (BMS) in 2021, Bank Panin Dubai Syariah (BPDS) in 2022 and 2023, IBU BPD Nagari (Sumatra Barat) in 2021 and 2023, and IBU BPD Jawa Timur in 2022. Each ICB and IBU has generally been able to carry out all of its objectives, namely Tahdzib al-fard (educating individuals), Iqamah al-adl (upholding justice), and Jabl al-Maslahah (Creating welfare). This research provides implications for further evaluation and development regarding the appropriate performance assessment of ICB and IBU and the following Sharia principles prioritizing the benefit of the people